The Development of Digital Pocket Book- Based Learning Media to Improve Students' Interest in Learning Social Sciences Subject - Ilma, Ilma Sya'wanah; Syafaatul Hidayati (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2023)
The use of digital-based learning media such as digital pocket books is very necessary in teaching and learning activities. The aim of this research is to develop digital pocket book media that is able to increase students' interest in learning in social studies subjects at BP FAI UMJ. The development research model uses ADDIE (Analysis, Design, Development, Implementation and Evaluation) with Research and Development (R&D) research methodology. The test subjects in this research were class VII students at SMP BP FAI UMJ, Kemang District, Bogor Regency for the 2020/2021 academic year with a total of 23 students. The data collection instruments used in this research were validation questionnaire instruments for material experts, media experts, teacher response questionnaire instruments and student interest questionnaire instruments. The results of the research show that material expert validation on digital pocket book media is 97% with very good criteria and media expert validation results are 100% with very good criteria. The results of the teacher response of 84% were very good criteria. The results from the student questionnaire were 85.97%. The results of the digital pocket book media product development show that there is an increase in students' interest in learning after being taught using digital pocket book media. This shows that the use of digital pocket book media is able to increase students' interest in learning in class VII social studies subjects.